Person job fit dan employee innovative work behavior terhadap kinerja individu: Toxic workplace environment sebagai moderasi - Ariyanti, Sindy Rosita Alvi; Pujianto, Wahyu Eko (Journal of Management and Digital Business, 2024)
This research analyses the relationship between a person's job fit, innovative work behaviour, and individual performance in a toxic workplace environment. In addition, this research was conducted to test whether the workplace environment can moderate this relationship. The method used is the structural equation model. The sample determination uses a purposive sampling technique, and are 80 respondents in a toxic workplace environment. Data collection was carried out by distributing questionnaires online via the WhatsApp application. The results of this study indicate that people's job suitability has no significant effect on individual performance, and innovative work behaviour has a significant effect on individual performance. Meanwhile, the workplace environment as a moderating variable weakens the relationship between a Person's job fit and Employee Innovative Work Behavior on individual performance (Toxic workplace environment as moderation). Person Job Suitability and Employee Innovative Work Behavior on Individual Performance Toxic Work environment as moderation.